The Influence of Applying the Singing Learning Method on Student Learning Outcomes in Mahfudzot Subjects at Pondok Modern Darussalam Gontor Putri Campus 8 - Fajri, Latifah Nurul; Jaenullah, Jaenullah; Pratiwi, Wiwied (International Journal on Advanced Science, Education, and Religion, 2025)
This research aims to determine the effect of applying the singing learning method on female students' learning outcomes in the subject Mahfudzot. The method used in this research is a quantitative research method with an approach Quasi Experimental Design and forms of research design Non equivalent control group design. This research was carried out at Pondok Modern Darussalam Gontor Putri Campus 8, Labuhan Ratu 6 East Lampung. In the even semester of the 2024-2025 academic year, the research subjects are class V KMI 1 and class V KMI 2. The population of each class is 30 female students. Collecting data on female students' learning outcomes from each class is by pretest and posttest. Analysis of this research data uses testing independent T-Test. The results obtained after testing were class V KMI 1 (control) had an average value of 45.67 while class V KMI 2 (experimental) had an average value of 72.33. Apart from that, it can also be seen that the value P-Value (sig.2-tailed) 0.000 < 0.05. So it can be said that H0 rejected and H1 It is accepted that from these results there is a significant difference in student learning outcomes between the experimental class which applies the singing learning method and the control class which applies the conventional method. Based on these results, it can be said that the students' learning outcomes by applying the singing learning method in the subject mahfudzot higher than the learning outcomes of female students who apply conventional methods in subjects mahfudzot.